Factors contributing to the delayed diagnosis of endometriosis—a systematic review and meta-analysis - Wenwei Li; Huiyan Feng; Qingjian Ye (Frontiers in Medicine, 2025)
BackgroundEndometriosis is a prevalent gynecological disorder that is estimated to affect approximately 10% of women of childbearing age globally. However, the condition remains significantly under-or misrecognized, and the mean time to diagnosis is several years. These delays result in increased symptom severity, diminished quality of life, and adverse long-term reproductive outcomes. Therefore, the aim of this systematic review and meta-analysis was to estimate the sources of diagnostic delay and their effects.MethodsThe articles were retrieved from PubMed, Cochrane, and Google Scholar databases after performing a rigorous literature search. The initial search yielded 2,348 records, and 10 articles were included in the final analysis. Causes of diagnostic delay were classified under patient, physician, and systems attributes. Random-effects analysis was used to estimate the overall SMDs with 95% confidence intervals (CIs). For the primary post hoc analysis, subgroup analyses and evaluation of heterogeneity (I2 statistic) were conducted. Publication bias was checked using Egger’s test and funnel plots.ResultsPatient-related factors demonstrated a significant pooled effect size (SMD: 1.94, 95% CI: 1.62–2.27, p < 0.001), with delays in seeking medical attention (SMD: 2.14, 95% CI: 1.36–2.92) contributing most prominently. Provider-related factors, including misdiagnosis and reliance on non-specific diagnostics, also had a substantial pooled effect size (SMD: 2.00, 95% CI: 1.72–2.28, p < 0.001), with low heterogeneity (I2 = 3%). System-related factors, such as referral pathways and geographic disparities, were not analyzed separately due to insufficient data for the subgroup. Funnel plot analysis showed no significant publication bias (Egger’s test p = 0.57).ConclusionThe results indicate that diagnostic delays in endometriosis are a function of multiple factors, with key contributions from patient and provider-related barriers. To close these gaps, targeted interventions such as public education to combat symptom normalization and stigmatization, more comprehensive provider training, and streamlined diagnostic pathways are needed. Future research can evaluate system-level changes and non-invasive diagnostic tools to reduce systemic delays further.